Soluble endoglin modulates the pro-inflammatory mediators NF-κB and IL-6 in cultured human endothelial cells - Varejckova, Michala; Gallardo-Vara, Eunate; Vicen, Matej; Vitverova, Barbora; Fikrova, Petra; Dolezelova, Eva; Rathouska, Jana; Prasnicka, Alena; Blazickova, Katerina; Micuda, Stanislav; Bernabeu, Carmelo; Nemeckova, Ivana; et al. (Life sciences, 2017)
AIMS: Endoglin is a transmembrane glycoprotein, that plays an important role in regulating endothelium. Proteolytic cleavage of membrane endoglin releases soluble endoglin (sEng), whose increased plasma levels have been detected in diseases related to the cardiovascular system. It was proposed that sEng might damage vascular endothelium, but detailed information about the potential mechanisms involved is not available. Thus, we hypothesized that sEng contributes to endothelial dysfunction, leading to a pro-inflammatory phenotype by a possible modulation of the TGF-β and/or inflammatory pathways. MAIN METHODS: Human umbilical vein endothelial cells (HUVECs) and Human embryonic kidney cell line (HEK293T) were treated with different sEng concentration and time in order to reveal possible effect on biomarkers of inflammation and TGF-β signaling. IL6 and NFκB reporter luciferase assays, quantitative real-time PCR analysis, Western blot analysis and immunofluorescence flow cytometry were used. KEY FINDINGS: sEng treatment results in activation of NF-κB/IL-6 expression, increased expression of membrane endoglin and reduced expression of Id-1. On the other hand, no significant effects on other markers of endothelial dysfunction and inflammation, including eNOS, peNOSS1177, VCAM-1, COX-1, COX-2 and ICAM-1 were detected. SIGNIFICANCE: As a conclusion, sEng treatment resulted in an activation of NF-κB, IL-6, suggesting activation of pro-inflammatory phenotype in endothelial cells. The precise mechanism of this activation and its consequence remains to be elucidated. A combined treatment of sEng with other cardiovascular risk factors will be necessary in order to reveal whether sEng is not only a biomarker of cardiovascular diseases, but also a protagonist of endothelial dysfunction.
Keywords: Gene Expression Regulation; Soluble endoglin; endoteliální buňky pupečníkové žíly (lidské); Inflammation; inhibitor diferenciace 1; HEK293 buňky; NF-κB; signální transdukce; Interleukin-6; HEK293 Cells; endoglin; Endothelial cells; Human Umbilical Vein Endothelial Cells; rozpustnost; Signal Transduction; Inhibitor of Differentiation Protein 1; zánět; lidé; Endoglin; interleukin-6; Humans; NF-kappa B; regulace genové exprese; IL-6; Solubility